THE APPLICATION OF THE PROBLEM-BASED LEARNING TEACHING MODEL IN IMPROVING STUDENTS' ABILITY TO SOLVE HIGHER ORDER THINKING SKILLS QUESTIONS - Fadhila Eka Putri; Sri Kartikowati; Mujiono Mujiono (Education Administration Study Program, School of Postgraduate Studies, Universitas Riau, 2023)
This study aimed to determine the increase in the ability to solve Higher Order Thinking Skills (HOTS) questions in the economics subject. This quantitative study employs a pre-experimental design with a pretest-posttest control group design. The instrument in this study used economic HOTS questions in the form of 15 multiple choice questions to determine the increase in ability to solve HOTS questions with the application of the Problem-Based Learning teaching model. It is known that the pre-test distribution data analysis obtained a mean of 58.64. In contrast, the post-test after being given a stimulus or treatment with the HOTS approach obtained a mean of 86.70, resulting in an increase in the results of the HOTS post-test after applying the Problem-Based Learning teaching model. There is a significant difference through the results of the students' pre-test and post-test, as evidenced by the t-test obtained t-count > t-table (6.855 > 1.675) and the Wilcoxon Sign rank test, which produces a value (asym.sig.(2-tailed)) is 0.000 <0.05. Then, the results of hypothesis H0 are rejected, and H1 is accepted. It can be concluded that there is an effect after applying the Problem-Based Learning teaching model in increasing the ability to solve HOTS questions